Description of Trichodorus iranicus sp. n. (Diphtherophorina, Trichodoridae) from Iran - Pedram, Majid; Pourjam, Ebrahim (Zootaxa, 2014)
Trichodorus iranicus sp. n. is described and illustrated based on morphological and molecular characters and morphometric data. It belongs to the T. lusitanicus morphospecies group based on the shape of the spicules and vaginal sclerotised pieces. Males have a body length of 844–942 µm, onchiostyle length of 59 µm, three cervical papillae (CP), curved spicules, 28–30 µm in length, with narrow mid-part, sometimes provided with a few bristles, and slightly developed manubrium. Females of the new species are 727–870 µm long with secretory-excretory pore located opposite anterior end of pharyngeal bulb, vagina length 46–57% of corresponding body width, with triangular to triangular-rounded sclerotised pieces 3.5 µm long, 1–2 µm apart from each other, and vulva a transverse slit. In its morphology, the new species resembles T. andalusicus, T. asturanus, T. azorensis, T. beirensis, T. lusitanicus, T. velatus and T. viruliferus and the morphological and morphometric differences separating T. iranicus from these known species are discussed. The D2-D3 region of 28S rDNA for the new species was amplified and the 679 bp newly-obtained sequence was used in a Bayesian inference (BI) analysis which confirmed the close relationship of the new species with T. lusitanicus morphospecies group members and placed it as a sister taxon to T. andalusicus in a well-supported clade that also includes T. asturanus.